Validity of the Richmond Agitation-Sedation Scale (RASS) in critically ill children - Kerson, Abigail Glicksman (J Intensive Care, 2016)
BACKGROUND: The Richmond Agitation-Sedation Scale (RASS) is a single tool that is intuitive, is easy to use, and includes both agitation and sedation. The RASS has never been formally validated for pediatric populations. The objective of this study was to assess inter-rater agreement and criterion validity of the RASS in critically ill children. METHODS: To evaluate validity, the RASS score was compared to both a visual analog scale (VAS) scored by the patient’s nurse, and the University of Michigan Sedation Scale (UMSS), performed by a researcher. The nurse completed the VAS by drawing a single line on a 10-cm scale anchored by “unresponsive” and “combative.” The UMSS was used to validate the sedation portion of the RASS only, as it does not include grades of agitation. For inter-rater agreement, one researcher and the patient’s nurse simultaneously but independently scored the RASS. RESULTS: One hundred patient encounters were obtained from 50 unique patients, ages 2 months to 21 years. Of these, 27 assessments were on children who were mechanically ventilated and 73 were on children who were spontaneously breathing. In validity testing, the RASS was highly correlated with the nurse’s VAS (Spearman correlation coefficient 0.810, p < .0001) and with the UMSS (weighted kappa 0.902, p < .0001). Inter-rater agreement between nurse- and researcher-assessed RASS was excellent, with weighted kappa of 0.825 (p < .0001). CONCLUSIONS: The RASS is a valid responsiveness tool for use in critically ill children. It allows for accurate assessment of awareness in mechanically ventilated and spontaneously breathing patients, and may improve our ability to titrate sedatives and assess for delirium in pediatrics.